Agonistic Behaviour in Luxury Branding - Sutrisna, Elaine (Curtin University, 2018)
This research extended the theory of agonistic behaviour from the field of biological sciences to consumer behavior, specifically in the context of luxury brands. A theoretical framework was developed, underpinned by the theory of agonistic behavior to examine the effects of perceived competition and perceived scarcity on consumer evaluation across three luxury product categories. The research contributes by developing and validating the theoretical framework using real-life scenarios and marketer-induced scarcity strategies in the luxury branding context.